Antibiofilm activity of bioactive hop compounds humulone, lupulone and xanthohumol toward susceptible and resistant staphylococci - Bogdanova, Katerina; Röderova, Magdalena; Kolar, Milan; Langova, Katerina; Dusek, Martin; Jost, Petr; Kubelkova, Klara; Bostik, Pavel; Olsovska, Jana (Research in microbiology, 2018)
Bacterial biofilms pose a serious medical problem due to their significant resistance to antimicrobials, and staphylococci are recognized as the most frequent cause of biofilm-associated infections. The hop plant (Humulus lupulus L.) contains substances that have been determined to act as anti-infective agents against bacteria, mainly in planktonic form. Therefore, we decided to investigate the antibiofilm properties of H. lupulus L.-derived compounds (humulone, lupulone and xanthohumol) against a selected group of Staphylococcus spp., including methicillin-susceptible and resistant strains. All tested hop compounds were shown to possess antimicrobial properties against all tested staphylococci, both planktonic and biofilm-dwelling, with no significant difference between resistant and susceptible strains. All compounds lowered the number of bacterial cells released from the biofilm, with the strongest effect seen for lupulone, followed by xanthohumol. Moreover, lupulone and xanthohumol were not only able to penetrate the biofilm and reduce the number of bacteria within it, but their higher concentrations (∼60 μg/mL for xanthohumol and ∼125 μg/mL for lupulone) reduced the number of surviving bacterial cells to zero.
Keywords: flavonoidy; Cell Survival; Microbial Sensitivity Tests; Flavonoids; Plant Extracts; terpeny; Humans; Humulus; mikrobiální testy citlivosti; lidé; antibakteriální látky; rostlinné extrakty; propiofenony; Terpenes; Propiophenones; buněčné linie; Cell Line; Anti-Bacterial Agents; biofilmy; Staphylococcus; Cyclohexenes; viabilita buněk; cyklohexeny; Biofilms